2010
DOI: 10.3944/aott.2010.2270
|View full text |Cite
|
Sign up to set email alerts
|

functional outcome and complications following PHILOS plate fixation proximal humeral fractures

Abstract: Objectives: Proximal humeral fractures account for approximately 5% of all fractures. New plating techniques have been developed to improve stability. The purpose of this study was to evaluate functional outcome following plate fixation with the Proximal Humeral Internal Locking System (PHILOS) and to analyze potential implant-related complications. Methods: The PHILOS plate was used for internal fixation of displaced proximal humeral fractures in 28 patients (20 females, 8 males; mean age 60.7±12.9 years). Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
55
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 18 publications
12
55
1
3
Order By: Relevance
“…There have been several recent studies which have demonstrated satisfactory outcomes following ORIF of proximal humeral fractures [25,[27][28][29][30][31][32]. Brunner et al [27] treated 158 fractures and at 1 year follow up noted a Constant score of 72.…”
Section: Open Reduction and Internal Fixationmentioning
confidence: 99%
“…There have been several recent studies which have demonstrated satisfactory outcomes following ORIF of proximal humeral fractures [25,[27][28][29][30][31][32]. Brunner et al [27] treated 158 fractures and at 1 year follow up noted a Constant score of 72.…”
Section: Open Reduction and Internal Fixationmentioning
confidence: 99%
“…Proksimal humerus kırıkları-nın tedavisinde kullanılan diğer cerrahi yaklaşım lateral deltoid split girişimdir. [1,2] Deltoid split yaklaşımla humerus başı, tüberculum majus, proksimal humeral şaftın lateral kısmı ve döndürücü manşet direkt görüntülenebilir. Bu yaklaşımın en önemli tehlikesi, aksiller sinirin seyri ve bu sinire ait varyasyonlardan kaynaklanmaktadır.…”
Section: Introductionunclassified
“…1 Their incidence is particularly higher in patients over 65 years age in whom they represent the most common fracture type. 2,3 Most proximal humerus fractures are stable, minimally displaced and can be managed conservatively.…”
Section: Introductionmentioning
confidence: 99%
“…The insertion of multiple polyaxial locking screws through the specific targeting device into humeral head fragment provides a fixed angle support in multiple planes, which should in theory, maintain the reduction achieved , while allowing for early mobilisation. 1 However inspite of all potential benefits significant level of construct failure and revision surgery with the use of proximal humerus locking plates have been reported particularly in patients over 65 years of age. reduction and internal fixation with a Philos plate (Synthes).…”
Section: Introductionmentioning
confidence: 99%